DISTRIBUSI BAKTERI NITRIFIKASI DI DANAU PAPARAN BANJIR STUDI KASUS : DI SUAKA PERIKANAN DANAU LOA KANG, KALIMANTAN TIMUR - Badjoeri, Muhammad (JURNAL BIOLOGI INDONESIA, 2006)
ABSTRACTDistribution of Nitrifying Bacteria in Floodplain Lake. Case Study in Lake LoaKang Fishery Reserve, East Kalimantan. Lake Loa Kang is a fishery reserve locatedin a floodplain system of River Mahakam. This floodplain lakes consists of severalhabitat types among the others are backswamp deposit lakes represented by Lake LoaKang and Lake Balikpapan. This two floodplain lakes exchange water with RiverMahakam and one of its tributary, the River Pela. Nitrification is one key ofmicrobiological process of nitrogen cycle in inland water. The nitrifying bacteria functionalgroup that mediated the process can be detected and identified by enrichment culture.This study was aimed to reveal feature of nitrification process in several floodplainhabitat types of Lake Loa Kang Fishery Reserve (LLFR) system with emphasize on thespatial distribution pattern of nitrifying bacteria. The results ofthe study will be utilizedas limnological database for development of conservation and restoration of Pesut habitat.Water samplings are conducted for three times in 2003, those were in dry season (June),transitional (August) and the rainy (Sept.). Results of the study showed that the numberof nitrifying bacteria is highest at connecting channel between floodplain lakes (L. BalikPapan) and River Mahakam and the lowest in small size ephemeral pond in LLFR (Lopak).Ex situ simulation of this biogeochemical cycle indicate a duration of 13 - 21 days tocomplete the nitrification process. The number of nitritation and nitratation bacteria inLake Loa Kang in the dry season is smaller compared to the number in rainy season. Theduration of nitrification process in LLFR suspected to be influenced by the number ofbacteria, organic material and season.Key words: Distribution,Floodplain, Lake Loa Kang Fishery Reserve, Nitrifying bacteria